PENGARUH PENGGUNA GAME DARING TERHADAP MOTIVASI BELAJAR BAHASA INDONESIA SISWA SMK - Emha Nuruzzaman (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
In the era of globalization and the rapid development of technology, online games or entertainment in the form of online games and in the form of multimedia, have become games that are fun and in demand by many people. Online games have their own charm that is addictive or addictive. The tendency to play online games is what will have a negative impact on users, especially among students. This phenomenon is very influential on the academic value of a student. The amount of time that is wasted so that you can play online games makes study schedules and school assignments that should be done by students at home to be neglected. This research method uses quantitative research methods and questionnaires as a means of collecting data. The purpose of this study was to determine the effect of online games on learning motivation of class XII students of SMK Plus Darusurur. The results of this study indicate that many students in class XII have online games and their academic scores are below the average score.